POTENSI BIJI MENGKUDU (Morinda citrifolia L.) SEBAGAI ANTELMINTIK TERHADAP Ascaris suum - Setya, Adhi Kumoro; Suwarmi, Sri (Media Farmasi Indonesia, 2018)
Abstract Parasitic infection from Genus Ascaris (Ascaris suum and Ascaris lumbricoides) is the parasite that most frequently causes worms in humans and livestock. This infection can cause intellectual retardation, cognitive and educational deficits with impacts on the nation productivity espesialy in children. It is known that a number of harmful synthetic drugs have side effects to health. In decades, mengkudu (Morinda citrifolia) is known to be useful in pharmacology to overcome health problems. In this fruit, there are seeds that have not been widely studied despite its benefits, and oftentimes, these seeds only go as waste product. The present research is aimed to show whether mengkudu seeds are potential to be exploited as antelmintic. The antelmintic ability of mengkudu seed extract was measured using regretion-probit analysis, and its pathological effects were tested through histologic painting. This research used five variations of concentration with three replicates. The worms per treatment were 4. The analysis result showed that lethal concentration (LC50) of 7.12% and lethal time (LT50) of 174 minutes. The histology of worms’ intestines demonstrates intestinal microfili that they become dull and their neural networks become tenuous. We report that mengkudu seed extract has antelmintic potency.